ANALISIS HASIL BELAJAR PESERTA DIDIK YANG MENGGUNAKAN SMARTPHONE KELAS VIII B DI SMP NEGERI 5 PONTIANAK - Lindawati Lindawati; Okianna Okianna; Aminuyati Aminuyati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis research was conducted at SMP Negeri 5 Pontianak. This research is titled "Analysis of Learning Outcomes of Learners Who Use Smartphone Class VIII B SMP Negeri 5 Pontianak". The purpose of this study is to find out the picture of learners' learning outcomes and the picture of the positive and negative impact of smartphone use on learners. The research method used is qualitative with descriptive form of research. The data source in this study is a student of class VIII B SMP Negeri 5 Pontianak who uses interview data and documentation. The results showed that the use of smartphones affects the learning outcomes of learners. Learning outcomes obtained by learners do not increase because participants always rely on smartphones in doing every task given by teachers and lack confidence in their abilities.Smartphones also have a positive impact such as learners easier to find information, increase knowledge, as a medium of entertainment, and facilitate communication. While the negative impact of smartphone use learners become lazy to read, lack confidence with their abilities, interfere with health, interfere with the concentration of learners' learning and affect the attitudes and behavior of learnersKeywords: Learners, Learning Outcomes, Smartphone Use